Correction: From Static to Interactive: Transforming Data Visualization to Improve Transparency. - Tracey L Weissgerber; Vesna D Garovic; Marko Savic; Stacey J Winham; Natasa M Milic (PLoS Biology, 2016)
[This corrects the article DOI: 10.1371/journal.pbio.1002484.].